2005
DOI: 10.1007/s00228-005-0036-4
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate medication prescribing in community-dwelling elderly people living in Iran

Abstract: Our findings indicate a high prevalence of inappropriate prescribing in elderly patients. Given the potential severity of this problem, further steps need to be implemented to prevent this occurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
38
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 31 publications
10
38
3
1
Order By: Relevance
“…Our finding is relatively agreeable and lower than the various similar other studies reported from India (23.59%), Nigeria (25.5%), USA (27.5%) and Iran (27.6%), 10,12,22,23 but higher than the study from Croatia (2.2%) and Turkey (9.8%) respectively. 24,25 In this study, 7.75% of total drugs prescribed were PIMs, which are in agreement with a study from India (7.45%) and Nigeria (7.88%) respectively.10,12 Among the 3 different categories in Beers criteria, in category 1 which is medications to be avoided in elderly, forms a major category of inappropriate use of drugs. From our study almost 18 different drugs were prescribed to these patients from category 1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our finding is relatively agreeable and lower than the various similar other studies reported from India (23.59%), Nigeria (25.5%), USA (27.5%) and Iran (27.6%), 10,12,22,23 but higher than the study from Croatia (2.2%) and Turkey (9.8%) respectively. 24,25 In this study, 7.75% of total drugs prescribed were PIMs, which are in agreement with a study from India (7.45%) and Nigeria (7.88%) respectively.10,12 Among the 3 different categories in Beers criteria, in category 1 which is medications to be avoided in elderly, forms a major category of inappropriate use of drugs. From our study almost 18 different drugs were prescribed to these patients from category 1.…”
Section: Discussionsupporting
confidence: 88%
“…12 An Iranian study by Azoulay et al showed that antihistamines were the most common PIMs, followed by NSAIDs and benzodiazepines. 25 In our study the PIMs were not prescribed with other comorbidity disease conditions, which comes under the category 2 of Beers criteria. Similar study by Veena et al from India also confirms our findings.…”
Section: Discussionmentioning
confidence: 96%
“…Other drugs like indomethacine and piroxicam, non -steroidal anti-inflammatory drugs; chlorzoxazone; muscle relaxant; amiodarone, a class III antiarrhythmic, amitryptyline, an antidepressant drug with sedative property and diazepam, a long acting sedative hypnotic were prescribed. When compared to the study from India, 6 our findings showed higher percentage for most of the drugs such as antihistamines 10.7%, dicyclomine 3.1%, diazepam 0.7% and amiodarone 0.7% while lower from the study in Iran 16 where antihistamines 29%, Non-steroid anti-inflammatory drugs (NSAIDs) 23% and benzodiazepine 16% were prescribed. In a study from Japan had reported the prevalence of PIM for different drugs like antihistamines (1.4%), antispasmodic (0.1%), amitriptyline (0%), and long acting benzodiazepines (0.1%).…”
Section: Discussioncontrasting
confidence: 68%
“…The average age found in this study (76.4 years) is similar to that found in other studies. 15,16 In our study, we found the average number of drugs prescribed was 5. The less number of drugs prescribed in our study compared to studies conducted in other countries might be due to a functional health insurance policy for the elderly in those countries which might have provided easier access to medications.…”
mentioning
confidence: 52%
“…Other researches show that the prevalence of institutionalized older people who take at least one PIM ranges from 27.6% to 46.2% (Ruggiero et al, 2010;Castellar et al, 2007;Azoulay et al, 2005). The prescription of PIM must follow judicious protocols, since their administration may double the odds of hospitalization of elderly people (Albert et al, 2010), as well as the demand for health services (Fick et al, 2008).…”
Section: Discussionmentioning
confidence: 99%